Health Insurance Programme in Nepal: Analysis of Implementation Status - Basnet, Jaya Prakash (BARUN Journal, 2024)
The government of Nepal started health insurance programme in 2017. Health service is under all levels government’s authority and responsibility. The health insurance programme is a citizen participatory programme which aims to reach the goal of universal health care coverage by the government and people’s right to receive special health services at a reasonable rate. This research is carried with the objective of finding the legal-institutional status of the programme and implementation status using a descriptive method. Participation of public and private health institutions in health service provision has made the service affordable, easy and convenient to the people. This scheme has reduced out-of-pocket expenditure of people in health service. The location of service providers mainly in urban areas, more distance for receiving service, and the complex process and referral system have made the service somehow problematic. Delays in payment of the claims and lower rate of services are discouraging health service providers in the scheme. Participatory management, cooperation and collaboration among stakeholders can make the programme more efficient and smoothly working. The finding of this research can help to strengthen the good practice of the programme and overcome the existing problems faced by the implementing agencies.